Analysis of Patient Safety Culture in Educational Dental Hospitals - Prabowo, Yoghi Bagus; Ahmad, Affan Noor Huda; Langit, Ken Sekar (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Patient safety culture is critical to the implementation of patient safety. An assessment of patient safety culture is required before beginning the process of developing a patient safety program. The findings are used to identify and evaluate potential units for development, as well as to inform policy decisions. The purpose of this study is to investigate the patient safety culture at Semarang's Educational Dental Hospital. Method: This study used a combination of analytic observation and cross-sectional design. The study's participants were health workers from Semarang Educational Dental Hospital. Random sampling was used to collect samples from up to 131 people in RSGMP X and 166 people in RSGMP Y. The information was gathered by distributing questionnaires based on the Agency for Healthcare Research and Quality (AHRQ) version 2.0. Result: The values of patient safety culture in RSGMP X and Y are the following: Error communication rates were 67.5% and 86.8%, respectively. Communication openness ranges between 74% and 76.7%. The handoff and information exchange rates are 73.3% and 85.1%, respectively. Patient safety is supported by hospital management at 80.5% and 81%, respectively. Organizational learning and continuous improvement have rates of 84.4% and 90.8%, respectively. Patient safety incidents were reported at rates of 59.5% and 63.1%, respectively. Responses to errors were 57.7% and 68.8%, respectively. The staffing and work rates are 72.9% and 71.5%, respectively. Supervisor and manager support for patient safety was 84.2% and 84.8%, respectively. Teamwork earned 84.4% and 88.5%, respectively. Conclusion: RSGMP X has four dimensions of strong patient safety culture and six dimensions of moderate culture, while RSGMP Y has seven dimensions of strong patient safety culture and three dimensions of moderate culture.